CAUSATIVE CONSTRUCTIONS IN JAVANESE - Yana Qomariana (Lingual: Journal of Language and Culture, 2016)
This paper aims at analyzing causative constructions found in Javanese. The data were takenfrom low register of Javanese spoken in Malang, a city in eastern part of Java Island throughobservation and note taking techniques. Furtehrmore they were analyzed descriptivelyagainst theory of causative construction by Kroeger (2004). The result showed that threetypes of causative construction: lexical, analytical and morphological causatives exist inEastern Javanese.